Apply the Zero Power Rule to create an equivalent expression to 4/3(−2+1^0).(1 point)

An equivalent expression to 4/3(−2+1^0) is 4/3(−2+ ).

5 answers

An equivalent expression to 4/3(−2+1^0) is 4/3(−2+1).
Solve the expression 2(1.6^0+7)−4.9^0.(1 point)
2(1.6^0+7)−4.9^0= .
2(1.6^0+7)−4.9^0 = 2(1+7)−1 = 2(8)−1 = 16−1 = 15.
Apply the Zero Power Rule of Integer Exponents to solve 2.3+(−1.478)^0.(1 point)
2.3+(−1.478)^0=
By applying the Zero Power Rule of Integer Exponents, any number raised to the power of 0 equals 1. Therefore, we have:

2.3 + (-1.478)^0 = 2.3 + 1 = 3.3.